2011
DOI: 10.5812/kowsar.1735143x.4223
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Adverse events and Sustained Viral Response in Children Undergoing Therapy for Chronic Hepatitis C Infection

Abstract: Article type: original ArticleBackground: Treatment of hepatitis C virus (HCV) infection with interferon (IFn) and ribavirin (RBV) is associated with adverse events, which may affect the patient's adherence to the treatment regimen and the treatment efficacy. Objectives: The aim of this study was to assess the sustained viral response (SVR) and interdependence between the haematological characteristics (leukocyte count, platelet count, and haemoglobin levels) in patients with chronic hepatitis C (CHC) infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…However, the Pt, WBC and Ne counts decreased in the SVR group, and they were significantly lower at the end of treatment in the SVR group compared with the NR/RR group. Our results are consistent with previous findings that leucopoenia and thrombocytopenia are significantly more pronounced in patients who achieved sustained virological response (8,25). We suggest that this difference is related to individual variations in pharmacokinetics and biochemical and physiological effects of drugs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the Pt, WBC and Ne counts decreased in the SVR group, and they were significantly lower at the end of treatment in the SVR group compared with the NR/RR group. Our results are consistent with previous findings that leucopoenia and thrombocytopenia are significantly more pronounced in patients who achieved sustained virological response (8,25). We suggest that this difference is related to individual variations in pharmacokinetics and biochemical and physiological effects of drugs.…”
Section: Discussionsupporting
confidence: 93%
“…Some of these adverse effects can be severe and require modification of the therapy dosage or withdrawal from therapy. However, a previous study by Pawlowska et al showed that alterations in haematological parameters are associated with response to therapy (8).…”
Section: Introductionmentioning
confidence: 93%
“…We read with interest the paper by Pawlowska et al (1) and we would like to add some comments. They conducted a retrospective cohort study of children with chronic hepatitis C (CHC) infection who completed treatment with ribavirin (RBV) plus pegylated IFN (peg-IFN) or recombinant IFN, and concluded that a mild decrease in hemoglobin levels , leukocyte and platelet counts during treatment may be the responsible factors for sustained viral response (SVR) induction.…”
mentioning
confidence: 99%